Guardians of the gut: influence of the enteric nervous system on the intestinal epithelial barrier - Bubeck, Marvin; Becker, Christoph; Patankar, Jay V. (Frontiers in Medicine, 2023)
The intestinal mucosal surface forms one of the largest areas of the body, which is in direct contact with the environment. Co-ordinated sensory functions of immune, epithelial, and neuronal cells ensure the timely detection of noxious queues and potential pathogens and elicit proportional responses to mitigate the threats and maintain homeostasis. Such tuning and maintenance of the epithelial barrier is constantly ongoing during homeostasis and its derangement can become a gateway for systemic consequences. Although efforts in understanding the gatekeeping functions of immune cells have led the way, increasing number of studies point to a crucial role of the enteric nervous system in fine-tuning and maintaining this delicate homeostasis. The identification of immune regulatory functions of enteric neuropeptides and glial-derived factors is still in its infancy, but has already yielded several intriguing insights into their important contribution to the tight control of the mucosal barrier. In this review, we will first introduce the reader to the current understanding of the architecture of the enteric nervous system and the epithelial barrier. Next, we discuss the key discoveries and cellular pathways and mediators that have emerged as links between the enteric nervous, immune, and epithelial systems and how their coordinated actions defend against intestinal infectious and inflammatory diseases. Through this review, the readers will gain a sound understanding of the current neuro-immune-epithelial mechanisms ensuring intestinal barrier integrity and maintenance of intestinal homeostasis.